Resolusi Konflik Nabi Muhammad SAW pada Peletakan Hajar Aswad - Darsini, Darsini; Musyafiq, Ahmad; Hilalinnisa, Khuriyatul; Mustaqim, Afif (IAIN Ponorogo, 2025)
This article discusses the conflict resolution by Prophet Muhammad (PBUH) in the case of the placement of the Black Stone, an important event before his prophethood. Through the perspective of conflict resolution theory, this study aims to explore how Prophet Muhammad (PBUH) successfully resolved the dispute between the Quraysh tribes. This research is a literature study employing a qualitative analysis model to interpret the actions of Prophet Muhammad (PBUH) in resolving the conflict over the placement of the Black Stone. The analysis indicates that Prophet Muhammad (PBUH) applied an approach reflecting the principles of effective conflict resolution, such as neutrality, a deep understanding of the conflicting parties, justice, and creativity in finding solutions. This study also reflects on the relevance of Prophet Muhammad's (PBUH) approach in contemporary conflict resolution. The theoretical implications of this study enrich conflict resolution scholarship by integrating Islamic perspectives into modern theoretical frameworks while affirming that Islamic teachings through the Quran and the exemplary practices of Prophet Muhammad (PBUH) provide a holistic foundation for sustainable conflict resolution.